1995
DOI: 10.1111/j.1439-0418.1995.tb01326.x
|View full text |Cite
|
Sign up to set email alerts
|

Selection for monocrotophos resistance in pear psylla, Cacopsylla pyri (L.) (Hom., Psyllidae)

Abstract: Pear psylla, Cacopsylla pyri (L.), adults collected from commercial pear orchards around Toulouse (France) were selected in the laboratory for resistance to monocrotophos. Resistance was obtained only when the insecticide selection pressure was continuous, but when some generations were not selected, resistance did not develop or even reverted. Resistance appeared to be stable after 30 generations of selection and stabilized at a level of 140-fold. The monocrotophos-selected strain was highly cross-resistant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…Laboratory selection pressure, did not markedly increase resistance over 17 or 23 generations implying a high level of homozygosity for resistance in the original field collections. This result differed from that observed by Berrada et al (1995) on C. pyri who, by selection with monocrotophos, increased the resistance rate from 25-fold to 130-fold in 18 generations. These authors also demonstrated that the resistance levels attained in the laboratory can only be maintained by exerting a constant selection pressure, a procedure that has not been tested in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Laboratory selection pressure, did not markedly increase resistance over 17 or 23 generations implying a high level of homozygosity for resistance in the original field collections. This result differed from that observed by Berrada et al (1995) on C. pyri who, by selection with monocrotophos, increased the resistance rate from 25-fold to 130-fold in 18 generations. These authors also demonstrated that the resistance levels attained in the laboratory can only be maintained by exerting a constant selection pressure, a procedure that has not been tested in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Tests with pyrethroids, amitraz, and carbamates did not reveal any particular tolerance of strains R1 and R2 to these insecticides. Berrada et al (1995) also noted strong cross-resistance between monocrotophos and phosmet (155-fold). Crossing of strains R1 and R2 to the susceptible strain indicated that resistance was semi-dominant.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Among the C. pyri resistance events in Europe the best known involve organophosphorates, pyrethroids and chitin inhibitors: in all documented cases a sharp decrease in pesticide activity was observed even after a few years of use. The active ingredient monocrotofos represents the best known case (Berrada et al, 1995 Table 4. Results of three field trials with spirodiclofen on three pear tree varieties Boselli & Cristiani, 2008).…”
Section: Evolution Of Resistance Of C Pyri To Pesticidesmentioning
confidence: 99%
“…Monocrotofos (an organophosphorous compound) is the best known example: the selection carried out by this insecticide on C. pyri populations led to an increase of pest resistance rate from 25-to 130-fold in only 18 generations (Berrada et al 1995). The same event occurred for Azinphos methyl (Buè s et al 2000).…”
mentioning
confidence: 99%